Tinjauan Pertimbangan Hakim dalam Memutuskan Perkara Wanprestasi pada Perjanjian Kredit Mobil Yang Dilakukan Debitur Terhadap PT. BANK PAN INDONESIA TBK (Studi Putusan Nomor 16/ Pdt.G/2022/PN.Tjk) - Hidayat, Rian Taufik; Anna Marpaung, Lintje (Universitas Medan Area, 2024)
This article seeks to examine the mechanism for settlement of default cases on car loan agreements and the judge's considerations in deciding a default case on a car loan agreement carried out by a debtor against PT. Bank PAN Indonesia based on Decision Number 16/Pdt.G/2022/PN.Tjk. The dialogue approach in this research is Juridical Normative, that is, an approach through library research (Library Research), or document study by examining and studying the rules or norms, rules, applicable legislation, and literature related to the issues at hand. researched and empirical approach, namely the approach carried out through direct research on research objects in order to collect primary data obtained directly in the field, through observation and interviews with informants related to the problems to be discussed in the research.